THE EFFECT OF COOPERATIVE LEARNING ON STUDENTS ECOLOGY ACHIEVEMENT AND INTERPERSONAL COMMUNICATION SKILL IN BIOLOGY EDUCATION STUDY PROGAM FKIP PAKUAN UNIVERSITY BOGOR - Indri Yani (UNIVERSITAS PAKUAN, 2019)
This research is aimed at finding out the effect of cooperative learning on students achievement in ecology and their interpersonal communication skill in Biology Education Study Program, FKIP Unpak Bogor. This research was conducted at Biology Education Study Program, FKIP Unpak Bogor, and academic year of 2017/2018. Population in this research is students of the fourth semester of Biology Education Study Program, FKIP Unpak Bogor. Cluster Random Sampling technique is used in choosing the sample. There are two classes chosen as the sample with 75 students. Quantitative approach is used with experimental method which consists of three variables. The first variable is Team Assisted Individualization model (TAI) which is a independent variable (X). The second variable consists of two dependent variables (Y) they are ecology learning achievement and interpersonal communication skill. Based on the data analysis and research result, it can be concluded that there is an effect of the use of Team Assisted Individualization model on ecology learning achievement in Biology Education Study Program, FKIP Unpak Bogor. Learning outcome of ecology and interpersonal communication skill on experimental group which taught using Team Assisted Individualization is better than the result of the control group. Team Assisted Individualization model is a model that can improve ecology learning outcome and interpersonal communication skill.